SOCIO-ECONOMIC EMPOWERMENT THROUGH COMMUNITY-BASED SHEEP FARMING PROGRAMS IN ISLAMIC RURAL SOCIETIES - Iis, Iis; Nurhayati, Sri; Kartika, Prita; Ahsan, Md Hafizi (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study examines the socio-economic empowerment fostered by a community-based sheep farming program in Desa Gelarwangi, KecamatanCidaun, Kabupaten Cianjur, within an Islamic rural society. Utilizing a qualitative approach with a case study method, the research explored the program's impact on economic development, social cohesion, and environmental sustainability. The research reveals that 1) the program has increased income for participants and fostered stronger community ties, 2) challenges such as seasonal feed shortages, limited access to veterinary services, and the need for formal training hinder its full potential. 3) The integration of sheep farming with local agricultural practices, mainly using sheep manure as fertilizer, has contributed to environmental sustainability and food security. 4)The lack of formal financial services and market integration limits further economic scalability. The study concluded that with continued governmental support and targeted interventions, community-based sheep farming programs have significant potential for sustainable socio-economic development in rural Islamic contexts, serving as a model for similar initiatives. The research contributes to the broader discourse on rural development, Islamic economics, and community-based agriculture.